Forest response and recovery following disturbance in upland forests of the Atlantic Coastal Plain - Schäfer, Karina V. R.; Renninger, Heidi J.; Carlo, Nicholas J.; Vanderklein, Dirk W. (Frontiers in Plant Science, 2014)
Carbon and water cycling of forests contribute significantly to the Earth’s overall biogeochemical cycling and may be affected by disturbance and climate change. As a larger body of research becomes available about leaf-level, ecosystem and regional scale effects of disturbances on forest ecosystems, a more mechanistic understanding is developing which can improve modeling efforts. Here, we summarize some of the major effects of physical and biogenic disturbances, such as drought, prescribed fire, and insect defoliation, on leaf and ecosystem-scale physiological responses as well as impacts on carbon and water cycling in an Atlantic Coastal Plain upland oak/pine and upland pine forest. During drought, stomatal conductance and canopy stomatal conductance were reduced, however, defoliation increased conductance on both leaf-level and canopy scale. Furthermore, after prescribed fire, leaf-level stomatal conductance was unchanged for pines but decreased for oaks, while canopy stomatal conductance decreased temporarily, but then rebounded the following growing season, thus exhibiting transient responses. This study suggests that forest response to disturbance varies from the leaf to ecosystem level as well as species level and thus, these differential responses interplay to determine the fate of forest structure and functioning post disturbance.